FREQUENCY OF CONVERSION TO OVERT HYPOTHYROIDISM IN PATIENTS WITH AND WITHOUT SUBCLINICAL HYPOTHYROIDISM - Anwer, Muhammad Shahzad; Hashim, Rizwan; Khan, Farooq Ahmed; Ijaz, Aamir (Journal of Ayub Medical College Abbottabad, 2012)
Background: Sub-clinical hypothyroidism (SCO) poses diagnostic and management difficulties for pathologists and clinicians. Cases of SCO are now diagnosed with increasing frequencies worldwide mainly because of availability of more sensitive methods for serum TSH, total T3 and free T4 assays. The rate of progression of SCO to overt hypothyroidism varies in different populations. Sub-clinical hypothyroidism has been suggested as a risk factor for hypothyroid complications. There is a need to identify and treat patients with SCO before they convert to overt hypothyroidism and develop complications. Objective was to compare the development of overt hypothyroidism in a cohort of patients of sub-clinical hypothyroidism and in subjects with normal thyroid function tests. Methods: It was Cohort study conducted at Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology, Rawalpindi. Hundred patients of SCO and almost equal number of age and sexmatched subjects with normal Thyroid function test (TFT) were enrolled as healthy controls. Subclinical hypothyroid patients and controls were followed for a period of one year on six monthly bases. The patients were examined for signs and symptoms of hypothyroidism and serum TSH, total T3 and free T4 were estimated. The clinical history, physical examination and thyroid function tests were recorded on the pre-designed Performa. Results: Fourteen (14%) out of 100 cases of the SCO patients developed overt hypothyroidism, SCO had 2.8 times more risk for conversion to overt hypothyroidism as compared to healthy controls. Moreover female gender and initial levels of serum TSH were the most important predictors for conversion of SCO to overt hypothyroidism. Conclusion: The frequency of conversion to overt hypothyroidism in SCO patients approaches 14% and was more commonly observed in female patients. Keywords: Subclinical hypothyroidism, thyroid stimulating hormone, thyroid function tests, overt hypothyroidism